The Use of Various Substrate Microbial Bamboo Stems for Rice Straw Fermentation and its effect on digestibility and fermentation product of Beef Cattle Ration - Chabib B.H; Sri Rahayu; Muhamad Bata (Pascasarjana Universitas Jenderal Soedirman, 2020)
This experiment investigated various substrate growth of bamboo stems microbes (BSM) in rice straw fermentation and its effect on dry matter digestibility (DMD), organic matter digestibility (OMD), NH3-N and VFA concentration. Materials were rumen fluid of beef cattle from the slaughterhouse. Basal diets consisted of rice straw and concentrate with ratio of 40 : 60 (% dry matter) were administered to five treatments namely P0 = untreated rice straw (control), P1 = Ammoniated rice straw, fermented rice straw using microbial bamboo stems grown on ammoniated rice straw (P2), rice bran (P3) and cassava waste (P4). The experiment used in vitro method was designed with Completely Randomized Design and the data were analyzed variance. The results showed that the treatment had no significant effect on dry matter digestibility (DMD), organic matter digestibility (OMD), NH3-N and VFA concentration (P>0,05). The fermentation process of microbial bamboo stems in rice straw with a level of 10% with different substrate did not able to increase the digestibility and products fermentation, but there tends that the rice bran and substrates can increase DMD and N-NH3 concentration